Estudo fotométrico e polarimétrico de regiões HII galácticas - Fabio Pereira Santos (2013)
Massive stars cause critical effects on the properties of the interstellar medium, ionizing, heating, evacuating the material, and consequently altering significantly the gas and dust spatial distribution. In such ionized environments, known as Hii regions, there is a strong relation between the characteristics of the interstellar medium and the young stellar population, with the properties of the magnetic field lines, which pervade the galactic disk. This relation may determine fundamental aspects of the influence of magnetic fields on the processes of star formation. In this research, our goal was to carry out a detailed analysis of star forming environments, including: the properties of the young stellar population; the evolutionary status and the morphology of the embedded stellar cluster; the shape of magnetic field lines and its relation with the interstellar medium; the features of dust grains from these regions. Therefore, we have used a set of polarimetric data (originated from OPD-LNA and CTIO), near-infrared photometric data (from the NTT-ESO/La Silla telescope and the 2MASS catalog), as well as optical (DSS) and mid/far-infrared observations (Spitzer, IRAS, MSX). We have focused particularly on two galactic star-forming regions, denominated RCW 41 and Sh 2-29. Both present massive stars within embedded clusters (with several lower mass young objects), and besides, exhibit quite complex interstellar medium sub-structures, such as filaments, dense cores, ionization fronts, etc. For RCW 41, we have found several pre-main sequence candidate stars, and have determined an age between 2:5 and 5:0 million years for the embedded cluster. Thecluster presents a spherical morphology, which is probably a consequence of the presence of a remnant core from the original cloud. The field lines are curved following the borders of the Hii region (at the neutral zone), and oriented radially towards the center, inside the ionized volume. This scenery is due to the expansion of the region and is supported by recent models of the evolution of Hii regions. Near the central cluster, we have found lower values of the polarization degree. Statistical analyses show a higher turbulence degree of magnetic fields in this region, highlighting the disturbance of the interstellar medium around the star-forming region. In the direction of Sh 2-29, the general view indicates the presence of a cluster embedded within a central interstellar cavity, whose expansion distorts the shape of magnetic field lines, and maybe also induces the formation of dense cores. Such cores are probably linked to new generations of young stellar objects. Over the border of the cavity, we have found evidence of the pilling-up of field lines. Around the cavity, the whole Hii region also seems to expand, generating an organized pattern along some directions. This results in significant variations of the turbulence degree along the entire area. The distributionof the ratio between the total-to-selective extinction values show a dual trend, suggesting both the effcts of coagulation, as well as destruction and fragmentation of interstellar grains. We conclude that the combined study of both the photometric features of the young stellar population, and the properties of the magnetic field lines, is fundamental in order todescribe a star-forming environment and determine many of the main physical processes acting on these systems.